Penerapan Hukum Pidana Terhadap Penyalahgunaan Izin Keimigrasian Menurut Undang-Undang RI No. 6 Tahun 2011 Tentang Keimigrasian (Studi Di Kantor Imigrasi Sumatera Utara) - Emilia, Liza; Nadirah, Ida (Universitas Ekasakti, 2024)
The era of globalization has made Indonesia a country that is open to the entry of foreign citizens to carry out activities in the fields of industry, tourism and other trade in Indonesia. In connection with this, in order to ensure the maintenance of stability from the influence of foreigners in Indonesia, regulations regarding the rights and obligations of foreigners are regulated in Law Number 9 of 1992 in conjunction with Law No. 37 of 2009 concerning Immigration which has been amended by Law Number 6 of 2011 concerning Immigration. To ensure that the provisions in this law are adhered to, this law also regulates criminal provisions that regulate several acts that qualify as criminal acts in the immigration sector committed by foreigners. Results of research on types of residence permits for foreign nationals in Indonesia based on Law Number 6 of 2011 concerning Immigration in the jurisdiction of the Class I North Sumatra Immigration Office. Article 1 of Law Number 6 of 2011 states that a permanent residence permit is a permit granted to foreigners. certain to reside and remain in the territory of Indonesia as a resident of Indonesia.